Capacity Building Of The State Administrative Court In Handling Onrechtmatige Overheidsdaad Cases: Challenges And Optimization Efforts - Igam Arya Wada; Yasmin Namira Andani; Faiqotul Himmah (Universitas Muhammadiyah Gresik, 2023)
The State Administrative Court (PTUN) in Indonesia faces a number of challenges in adjudicating cases of onrechtmatige overheidsdaad, which is an unlawful act of government administration. The new regulation through Supreme Court Regulation (PERMA) Number 2 of 2019 gives the PTUN clearer authority in adjudicating cases like this. However, the problem of unclear administrative law concepts and undetailed regulations in PERMA still hamper the legal process. This research aims to address the problem. With a focus on increasing the capacity of PTUN in dealing with onrechtmatige overheidsdaad cases. The study proposes five important steps to achieve this goal. First, it is necessary to increase the capacity of PTUN through increased budget allocation, human resources, and technology utilization. Secondly, it is necessary to simplify the proceedings in administrative law and mediation should be applied as an effective dispute resolution method. Third, the study suggests evaluation of similar cases as a first step in resolving cases, and mediation should be considered to reduce the backlog of cases that slow down the process. Fourth, it is necessary to strengthen law enforcement authority through the establishment of an independent law enforcement body that can impose sanctions for violations of PTUN decisions. Finally, it is necessary to increase public awareness about their rights and procedures for filing a lawsuit to PTUN through the establishment of legal information centers and education campaigns. The result of this research is a series of concrete solutions that can help PTUN in facing the challenges of adjudicating onrechtmatige overheidsdaad more effectively, ensuring better legal protection for the community, and ensuring government compliance with PTUN decisions.